(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the interpretation of myth, legend, and fairy tale in literature, analyzing their origins, functions, thematic elements, symbolic significance, and adaptations through history. Myths, legends, and fairy tales constitute foundational narratives within human culture and literature. These narrative forms, while sharing similarities, possess unique characteristics that influence their role in literary tradition. Drawing from interdisciplinary perspectives in folklore studies, literary criticism, and cultural anthropology, this study elucidates how these genres shape and reflect societal values, collective unconscious, and the human psyche.